81.7k views
4 votes
Help me with this equation from hw step by step please

Help me with this equation from hw step by step please-example-1
User Pikanezi
by
5.9k points

1 Answer

4 votes

Answer:

b1 = (2A/h) - b2

Step-by-step explanation:

The initial equation is:


A=(1)/(2)h(b_1+b_2)

To solve for b1, multiply both sides by 2


\begin{gathered} 2\cdot A=2\cdot(1)/(2)h(b_1+b_2) \\ 2A=h(b_1+b_2) \end{gathered}

Then divide both sides by h to get:


\begin{gathered} (2A)/(h)=(h(b_1+b_2))/(h) \\ (2A)/(h)=b_1+b_2 \end{gathered}

Now, subtract b2 from both sides:


\begin{gathered} (2A)/(h)-b_2=b_1+b_2-b_2 \\ (2A)/(h)-b_2=b_1 \end{gathered}

Therefore, the solution is:


b_1=(2A)/(h)-b_2

User Mgautierfr
by
5.6k points